The influence of prehospital time on trauma patients outcome: A systematic review. Issue 4 (April 2015) - Harmsen, A.M.K.; Giannakopoulos, G.F.; Moerbeek, P.R.; Jansma, E.P.; Bonjer, H.J.; Bloemers, F.W.
Abstract: Objective: Time is considered an essential determinant in the initial care of trauma patients. Salient tenet of trauma care is the 'golden hour', the immediate time after injury when resuscitation and stabilization are perceived to be most beneficial. Several prehospital strategies exist regarding time and transport of trauma patients. Literature shows little empirical knowledge on the exact influence of prehospital times on trauma patient outcome. The objective of this study was to systematically review the correlation between prehospital time intervals and the outcome of trauma patients. Methods: A systematic review was performed in MEDLINE, Embase and the Cochrane Library from inception to May 19th, 2014. Studies reporting on prehospital time intervals for emergency medical services (EMS), outcome parameters and potential confounders for trauma patients were included. Two reviewers collected data and assessed the outcomes and risk of bias using the STROBE-tool. The primary outcome was the influence on mortality. Results: Twenty level III-evidence articles were considered eligible for this systematic review. Results demonstrate a decrease in odds of mortality for the undifferentiated trauma patient when response-time or transfer-time are shorter. On the contrary increased on-scene time and total prehospital time are associated with increased odds of survival for this population. Nevertheless rapid transport does seem beneficial for patients suffering penetrating trauma, in particular hypotensive penetratingly injured patients and patients with a traumatic brain injury. Conclusion: Swift transport is beneficial for patients suffering neurotrauma and the haemodynamically unstable penetratingly injured patient. For haemodynamically stable undifferentiated trauma patients, increased on-scene-time and total prehospital time does not increase odds of mortality. For undifferentiated trauma patients, focus should be on the type of care delivered prehospital and not on rapid transport.